An annotated checklist of terrestrial flatworms (Platyhelminthes: Tricladida: Geoplanidae) from Mexico, with new records of invasive species from a citizen science platform and a new nomen dubium - Luna, Manuel De; Boll, Piter Kehoma (Zootaxa, 2023)
A checklist of species of terrestrial flatworms (Platyhelminthes: Tricladida: Geoplanidae) recorded for Mexico is compiled, listing 11 species. Five are directly referenced in the literature: Bipalium kewense Moseley, 1878, Bipalium vagum Jones & Sterrer, 2005, Diporodemus yucatani Hyman, 1938, Geoplana multipunctata Fuhrmann, 1914, and Pseudogeoplana nigrofusca (Darwin, 1844); and one species had been indirectly mentioned for the country: Parakontikia ventrolineata (Dendy, 1892), which was described from material intercepted in the USA in a shipment of ornamental plants from Mexico. Mexican records from the citizen science platform iNaturalist were reviewed, revealing the presence of five widely distributed invasive species: Caenoplana coerulea Moseley, 1877, recorded in Ciudad de Mexico; Endeavouria septemlineata (Hyman, 1939), recorded in Ciudad de Mexico, Estado de Mexico, Hidalgo, Jalisco, Morelos, and Oaxaca; Dolichoplana carvalhoi Corrêa, 1947, recorded in Jalisco; Dolichoplana striata Moseley, 1877, recorded in Morelos, Nuevo Leon, Quintana Roo, Tamaulipas, and Veracruz; and Rhynchodemus sylvaticus (Leidy, 1851), recorded in Jalisco. The presence of Parakontikia ventrolineata is confirmed for the country, being recorded in Ciudad de Mexico, Estado de Mexico, Hidalgo, Jalisco, Michoacan, Puebla, Queretaro, and Veracruz. The original description of Pseudogeoplana nigrofusca was revisited and compared to subsequent descriptions and keys, noting that the specimens are not conspecific and that the original description is too vague to accurately identify the species, therefore, this taxon is hereby relegated as a nomen dubium. A key for the higher taxa (subfamilies and tribes) of the North American terrestrial flatworms is proposed.